2019
DOI: 10.1007/s40843-019-1227-7
|View full text |Cite
|
Sign up to set email alerts
|

Capillary shrinkage of graphene oxide hydrogels

Abstract: Conventional carbon materials cannot combine high density and high porosity, which are required in many applications, typically for energy storage under a limited space. A novel highly dense yet porous carbon has previously been produced from a three-dimensional (3D) reduced graphene oxide (r-GO) hydrogel by evaporation-induced drying. Here the mechanism of such a network shrinkage in r-GO hydrogel is specifically illustrated by the use of water and 1,4dioxane, which have a sole difference in surface tension. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 43 publications
0
28
0
3
Order By: Relevance
“…The generated capillary pressure is directed to the concave liquid surface, the force along the graphene sheet can be used as the driving force for the removal of water from the fiber, and the force perpendicular to the graphene sheet will compress the graphene sheet, inducing shrinkage of the fiber. [ 22,28 ] It is demonstrated that a denser structure may be obtained by introducing graphene than that only with CNT in the fiber, indicating better mechanical properties. [ 29 ] When further increase the graphene content, the mechanical properties have a little decrease for the hardness increase of the fiber.…”
Section: Resultsmentioning
confidence: 99%
“…The generated capillary pressure is directed to the concave liquid surface, the force along the graphene sheet can be used as the driving force for the removal of water from the fiber, and the force perpendicular to the graphene sheet will compress the graphene sheet, inducing shrinkage of the fiber. [ 22,28 ] It is demonstrated that a denser structure may be obtained by introducing graphene than that only with CNT in the fiber, indicating better mechanical properties. [ 29 ] When further increase the graphene content, the mechanical properties have a little decrease for the hardness increase of the fiber.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the capillary drying technology was employed to shrink this hydrogel into a dense monolith (∼20 × volume contraction), yielding the SiMP@C-GN product. Specifically, the hydrogel was subjected to an evaporation-induced drying at 70°C for 48 h under air and atmospheric pressure [ 22 , 23 , 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…. 在进一步的研 究中, Ma等人 [68] 将HOGS采用凝胶毛细致密化方法 [69] 制备了HOPC(highly ordered and compact porous carbon), 提出一种空间电荷密度(spatial charge density,…”
Section: Dvag在混合超级电容器中的应用unclassified